Squeezed light and self-induced transparency in mercury-filled hollow core photonic crystal fibers - Vogl, Ulrich; Joly, Nicolas Y.; Russell, Philip St. J.; Marquardt, Christoph; Leuchs, Gerd (Proceedings 2015 European Conference on Lasers and Electro-Optics - European Quantum Electronics Conference, CLEO/Europe-EQEC 2015, 2015)
We successfully demonstrate squeezing of nanosecond pulses via self-induced transparency in a system of mercury vapor confined in a hollow core kagomé-style fiber.
CRIS-Team Scopus Importer:2022-06-05